Analisis Penilaian Kesehatan Keuangan Lembaga Penjamin Dengan Menggunakan Surat Edaran OJK Nomor 18/SEOJK.05/2018 - Anggraeni Novitasari; Kristianingsih Kristianingsih; Hasbi Assidiki Mauluddi (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to analyze the financial health of. the Sharia Guarantee Institution for the period 2014 to 2018 using liquidity ratio analysis, Gearing Ratio, and Profitability using analysis techniques of the Health Level of the Guarantee Company Financial Institution based on theIRegulationIof the Financial Services Authority (SAL SEOJK) Number 18 /SEOJK.05/2018. This research is a descriptive research type, which describes the financial performance of PT Asuransi Jamkrindo Syariah and PT Penjaminan Jamkrindo Syariah. The data research method used in this research. is the documentation method. The type of data used in the research is secondary data, which is obtained from the annual financial reports of PT Asuransi Jamkrindo Syariah and PT Penjaminan Jamkrindo Syariah for the period 2014 to 2018. The results obtained in this study are the level of health at PT Asuransi Askrindo Syariah and PT Penjaminan Jamkrindo. This Sharia falls into a fairly healthy category for five years. Whereas for 2014, PT Penjaminan Jamkrindo Syariah received an unhealthy category level. This is supported by the results of research on 1) the gearing ratio of the two companies that received a very poor category for five years period 2) the performance in the liquidity ratio shows that PT Penjaminan Jamkrindo Syariah received a very poor category in the first two years of the period while PT Asuransi Asuransi Askrindo Syariah received very good category value in five years period 3) the profitability ratio of the two companies, PT Penjaminan Jamkrindo Syariah got a pretty good category in 2014 and got a very good category in the following year period, PT Asuransi Askrindo Syariah got a good category score in 2017 while the other period of the year gets very good category.